Plan estratégico institucional para la empresa pública municipal de agua potable, alcantarillado y saneamiento básico del cantón Pedro Moncayo EPEMASAPM. - Ayala, Christian E. (2021)
This paper presents a proposal for an institutional strategic plan for the year 2021-2025 that has the balanced scorecard for EPEMASA-PM. EPEMASA-PM has developed several strategic plans, however, these have not been articulated with the plan of national development or with the objectives of sustainable development, therefore the present research study formulates the theoretical foundations, analyzed the concepts of strategic planning, its importance within the company and legal basis, the situational analysis of the Institution was developed, where the methodology to be developed as the investigation was established;